Electrical conductivity analysis of extrusion-based 3D-printed graphene - R, Hushein; Shajahan, Mohamed Iqbal; Čep, Robert; Salunkhe, Sachin; Murali, Arun Prasad; Sharad, Gawade; Mohamed Abdelmoneam Hussein, Hussein; Abouel Nasr, Emad (Frontiers in Materials, 2024)
Nowadays, research has shown the 3D printing method has emerged for printing a functionalized component. Graphene nanomaterial has an enormous conducting property that can compete with conducting materials like copper and silicon. This paper describes the electrical conductivity investigation of 3D printed graphene nanomaterial in extrusion-based 3D printing methods. In Extrusion, two different approaches of the 3D printing methods were used to print the Graphene-based structure, such as the Fused Deposition Modeling (FDM) method and Direct Ink Writing (DIW) method. Both printing methods follow the two printing processes and select material forms. Selection of testing was made to analyze the characterization variations of printed material such as XRD, TGA Analysis, Viscosity, Raman Shift and SEM analysis, which shows the changes of effect in the conductivity due to various parameter differences in both the printing methods. A four-point probe technique was used to analyze the electrical conductivity of the two different methods. These analysis results prove that the characterisation variations differ in the FDM and DIW printed models.